Morality-Induced Leakage and Decentralized Environmental Policy - Thomas Eichner; Marco Runkel (CESifo GmbH, 2025)
Within a two-country model, this paper identifies a novel emission leakage channel that is caused by moral behavior of (atomistic) consumers. In a non-cooperative emission tax game between the countries, the leakage effect lowers the governments' marginal benefit of emission taxation, so equilibrium emission tax rates are even lower and the emission levels even higher than in the business-as-usual without moral consumers. The detrimental effect of consumer morality may remain, if governments behave morally, too, and may even be exacerbated under country asymmetries. It disappears, if governments choose emission caps, since the caps fix national emissions and avoid morality-induced leakage.
Keywords: H23; H71; Q58; 330; moral behaviour; emissions; tax; cap; leakage